Enhanced electrocatalytic reduction of CO2 to formate via doping Ce in Bi2O3 nanosheets. Issue 10 (11th April 2022) - Li, Xiao; Qian, Ningkang; Ji, Liang; Wu, Xingqiao; Li, Junjie; Huang, Jingbo; Yan, Yucong; Yang, Deren; Zhang, Hui
Abstract : Ce-doped Bi2 O3 nanosheets were synthesized and exhibited substantially enhanced catalytic selectivity and activity for ECR relative to undoped ones. Abstract : Formate is considered as the most economically viable product of the prevalent electrochemical CO2 reduction (ECR) products. However, most of the catalysts for ECR to formate in aqueous solution often suffer from low activity and limited selectivity. Herein, we report a novel Ce-doped Bi2 O3 nanosheet (NS) electrocatalyst by a facile solvothermal method for highly efficient ECR to formate. The 5.04% Ce-doped Bi2 O3 NSs exhibited a current density of 37.4 mA cm −2 for the production of formate with a high formate faradaic efficiency (FE) of 95.8% at −1.12 V. The formate FE was stably maintained at about 90% in a wide potential range from −0.82 to −1.22 V. More importantly, density functional theory (DFT) calculations revealed that Ce doping can lead to a significant synergistic effect, which promotes the formation and the adsorption of the OCHO* intermediate for ECR, while significantly inhibiting the hydrogen evolution reaction via depressing the formation of *H, thus helping achieve high current density and FE. This work provides an effective and promising strategy to develop efficient electrocatalysts with heteroatom doping and new insights for boosting ECR into formate.